Mathematics, Software and YouTube: Possibilities for teachers and students in the classroom (Research, Society and Development, 2019)
Students are familiar and have easy access to smartphones, tablets, computers and applications and enjoy using them. Thus, the purpose of this article is to present a lesson proposal that uses digital technologies and its resources for the teaching-learning process in the mathematics discipline. This is a bibliographical review article. Thus, from the review: we identify the challenges and potentialities of Digital Information and Communication Technologies - TDIC applied to Education; we pointed out the main difficulties in teaching-learning "second degree function graph" content and suggested a lesson plan for teaching this content in math classes using two resources: GeoGebra software and videos on YouTube. The literature and the potentialities and characteristics of the suggested resources demonstrate how the proposal can contribute to a better understanding of the content, for example, in the student's visualization of the function graph. Thus, we consider that the proposal presented favors the teaching-learning process.